Estimation of economic cost of forest fire prevention and control - Osei-Fosu, Anthony Kofi (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of Master of Arts Degree in Economics.